Increased frequencies of human Th-17 CD4+ T-cells and decreased T-regulatory cells in patients with early and advanced metabolic dysfunction-associated steatotic liver disease - Supruniuk, Elżbieta; Grubczak, Kamil; Parfieniuk-Kowerda, Anna; Flisiak, Robert; Moniuszko, Marcin; Jaroszewicz, Jerzy; Chabowski, Adrian; Świderska, Magdalena (Frontiers in Immunology, 2025)
BackgroundDysregulation of immune responses may influence the progression of metabolic dysfunction-associated steatotic liver disease (MASLD) to metabolic dysfunction-associated steatohepatitis (MASH). Our recent data suggest the role of Th17-related cytokines in fibrosis advancement in MASLD. Herein, we aimed to analyze T-regulatory and Th17-producing T-lymphocytes by flow cytometry with respect to MASLD progression.MethodsExtensive immunophenotyping was performed in a subset of 30 patients with MASLD diagnosed by elastography and ultrasonography and 15 healthy controls (HCs). Ex-vivo surface markers (CD4, CD25, CD127) and intracellular cytokine expressions (IL-10, IL-17, Foxp3, RORgt) were analyzed by flow cytometry (BD FACS-Calibur). Plasma concentrations of selected interleukins such as IL-10, IL22, and IL-17A were measured by ELISA.Results19/30 (63%) of MASLD patients were diagnosed with steatosis with inflammation (advanced MASLD) as compared to simple steatosis (early MASLD) using elastography. The percentage of IL-17-producing cells among CD4(+) T-lymphocytes was two-fold more frequent (1.70% vs. 0.73%), while of T-regulatory cells (CD4+CD25+Foxp3+, T-regs) lower (3.57% vs. 6.56%) in advanced MASLD compared to HCs. This resulted in an aberrated ratio of Th17 to Tregs in MASLD (p=0.004). The frequency of T-regulatory cells (CD4+CD25+Foxp3+, Tregs) declined also in the advanced MASLD patients (3.57%) compared to the early stage disease (5.16%). Importantly, IL-10 and IL-17A serum levels positively correlated with CD4+IL-17+/CD4+CD25+Foxp3+ ratio. Plasma IL-10/IL-17A ratio and IL-10/IL-22 ratio significantly differed between F0 fibrosis vs. moderate (F2).ConclusionsThe imbalance between Th17 and T-regulatory immune responses is present not only at cytokine level but also at a cellular level in MASLD. Especially in advanced disease, a higher percentage of IL-17 producing T-cells is coupled with the lower number of T-regulatory cells.